Phenomenological Analysis in Sexy Killers Documentary Film - Agnes Yusuf (Epistemik Press, 2020)
Coal and Steam Power Plant (PLTU) are one source of energy that is capable of producing electrical energy. The amount of profits generated in the management of the coal business was utilized by a handful of people. They are a group of political elites, also known as political oligarchs, who freely enter and control the coal industry and all its policies. These political oligarchs utilize the momentum of the General Election to engage the private sector, obtain financial support and support, and legitimize the status of power through contestation, which provides a destructive force on the ecology and the lives of many people. The production team involved responded to the imbalance of hegemony produced by the political oligarchy through the screening of the documentary film Sexy Killers simultaneously, a week before the election took place. This study uses descriptive qualitative methods and phenomenological analysis, which is combined with the theory of hegemony and the symbolic interactionism. The data collection process used is in-depth interviews, documentation and data studies. The results of research from the production process carried out by the production team of the documentary film Sexy Killers are making the film an alternative media that becomes a counter-hegemony by dismantling the depravity of the system carried out by the political oligarchy and how they are involved in the coal mining business and PLTU; as well as being a program for education and criticism of conventional media.